Changes in soil microbial community composition and organic carbon fractions in an integrated rice–crayfish farming system in subtropical China - Guohan Si (Nature Portfolio, 2017)
Abstract Integrated rice–crayfish farming system is a highly efficient artificial ecosystem in which the rice (Oryza sativa) variety ‘Jianzhen 2′ is cultivated in waterlogged paddy fields along with crayfish (Procambarus clarkii). We investigated soil carbon fractions and microbial community structure by phospholipid fatty acids (PLFA) analysis in a 10-year field experiment using an integrated rice–crayfish (CR) model and a rice monoculture (MR) model at soil depths of 0–10 cm, 10–20 cm, 20–30 cm, and 30–40 cm. Compared with the MR model, the CR model had significantly more total organic carbon, particulate organic carbon, and dissolved organic carbon contents in all of the layers examined and microbial biomass carbon content in the 20–40 cm layer. Principal components analysis revealed that microbial community composition in the CR model differed from that in the MR model in the 20–30 cm layer. Higher proportions of gram–negative bacteria, aerobic bacteria and fungi in the 20–30 cm soil layer were observed for the CR model than the MR model. These results indicate that the CR model increases soil carbon levels, and strongly affects microbial community composition and structure in the deeper layers of soil, thereby accelerating subsurface soil nutrient cycling.